Pre-Service Teachers Experiences during Teaching Practice in South Africa: Challenges and Solutions - Oyinlola Omolara Adebola (JETL (Journal of Education, Teaching and Learning), 2022)
Pre-service teachers who want to become professional teachers are mandated to go for teaching practice at schools to implement the skills learnt in the classroom. Therefore, it is crucial for proper and adequate preparation at various schools where they will be teaching.  Unfortunately, experiences from pre-service teachers, literature, and observations have testified that schools do not prepare enough, especially in resources. To address this issue, the study identified challenges pre-service teachers encountered during teaching practice and explored the possible solutions pre-service teachers faced. The study adopted Transformative Leadership Theory (TLT) as a theoretical framework, Participatory Research (PR) as research design, while Transformative Paradigm TP was adopted to lens the study.  The selection of participants was done using a random sampling technique in order to be fair and unbiased. So, 10 out of 40 reflective assessments submitted by final year students were selected. Student reflection was used as a data collection method, while Thematic Analysis (TA) was adopted to analyse the data generated. The findings show that schools do not adequately prepare to receive pre-service teachers for teaching practice. It thereby recommended that schools with the intervention of the government, should try as much as possible to render support, especially in the area of educational resources, since there cannot be effective teaching in its absence. Again, the study recommends that schools orient learners about their perspectives towards pre-service teachers. .